Gross Split Contract Framework Regulation on the Caring for People - Kirana Intaniasari (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2020)
This study aims to determine the model of oil and gas governance in Indonesia in terms of the interests of the State to protect natural resources that should be controlled for maximum use for the prosperity of the people. This study is based on the results of normative legal studies that are descriptive. The type of data used is secondary data obtained from literature study data collection techniques, which are then analyzed by carrying out systematic interpretation of the law. Systematic means, making a classification of written legal materials, to facilitate the work of analysis and construction. The results of this study show that oil and gas management arrangements began in the Dutch colonial period and continue to change with the times up to now, specifically the regulation of upstream oil and gas. Upstream oil and gas management has changed several times, namely the Concession system, the Contract of Work system, Production Sharing Contract (PSC) and finally the Gross Split Production Sharing Contract. The emergence of Gross Split aims to improve the PSC system and improve the efficiency and effectiveness of oil and gas production sharing patterns. Even though Gross Split still has weaknesses, but when compared to the previous system, Gross Split is more in line with the country's goal of being as broad as possible for the people. Keywords: Mining; Gross Split; Welfare State.